Medicinal Herbs: Myths and Facts are they all safe? - Dash, G. K.; Sahu, M. R. (Pharmacognosy Reviews)
There has been a virtual explosion of interest in all kinds of alternative therapies, in particular those, which have been around for thousands of years. Naturally, in an illness where there is no "cure" and in which pharmaceutical drugs typically produce side effects, people look for other remedies. The use of herbal heritage has become a part of general health care by the tribes since time immemorial. The use of modern medicines of synthetic origin is believed to impart dramatic results in a short span in the therapeutic field has a hidden drawback of serious afterward consequences on the health on prolonged treatment due to various pathological, pharmacological and chrono-pathological parameters of the mankind.